Synergistic effects and correlating polarity parameters in binary mixtures of ionic liquids - Beniwal, Vijay; Kumar, Anil (Chemphyschem, 2015)
Understanding how a chemical reaction proceeds in solution requires precise knowledge of solute-solvent interactions. Certain issues involved in ionic liquid binary mixtures are still not clearly understood, including: 1) the effects of hydrogen-bond-acceptor basicity () of solvents on the synergistic effects found in ionic liquid-alcohol mixtures, 2) the interrelation between the polarity parameters in binary mixtures, and 3) the application of a model for the description of normalised electronic transition energy for all the binary mixtures. Here, a detailed analysis of polarity parameters in both hydrophilic and hydrophobic ionic liquids has been carried out. A three-parameter model developed by Roses et al. [J. Chem. Soc. Perkin Trans. 2 1997, 13411348] was found to be applicable to all the binary mixtures, and synergistic effects are generated as a result of high values of alcohols compared with those of the ionic liquids. A strong correlation was observed in the values and hydrophobicities of pure ionic liquids, suggesting that values can play a role in describing synergism.
Keywords: green chemistry; ionic liquids; liquids; noncovalent interactions; solvent effects

Spectacular rate enhancement of the diels-alder reaction at the ionic liquid/n-hexane interface - Beniwal, Vijay; Manna, Arpan; Kumar, Anil (Chemphyschem, 2016)
The use of the ionic liquid/n-hexane interface as a new class of reaction medium for the Diels-Alder reaction gives large rate enhancements of the order of 10(6) to 10(8) times and high stereoselectivity, as compared to homogeneous media. The rate enhancement is attributed to the H-bonding abilities and polarities of the ionic liquids, whereas the hydrophobicity of ionic liquids was considered to be the factor in controlling stereoselectivity.
Keywords: Diels-Alder reaction; Interfaces; ionic liquids; kinetics; stereoselectivity